Prescribing Practice in Inpatients Versus Outpatients With Schizophrenia Initiating Treatment With Second-Generation Antipsychotics: A Naturalistic Follow-Up Study. Issue 6 (December 2016) - Edlinger, Monika; Rettenbacher, Maria A.; Kemmler, Georg; Biedermann, Falko; Widschwendter, Christian G.; Fleischhacker, W. Wolfgang; Hofer, Alex
Abstract : Objective: The primary objective of this study was to investigate whether the choice and dosage of antipsychotic medication differ between patients with schizophrenia starting treatment in an inpatient or outpatient unit. In addition, we investigated whether the reason for the introduction of new antipsychotic medication had an impact on the treatment setting and whether the use of benzodiazepines differed between inpatients and outpatients. Method: From October 1997 to September 2010, patients with a schizophrenia spectrum disorder according to the International Classification of Diseases, Tenth Revision aged between 18 and 65 years were allocated to a naturalistic drug-monitoring program when starting treatment with a second-generation antipsychotic drug. Psychopathological symptoms were rated at baseline and after 1, 2, 4, and 8 weeks of treatment using the Positive and Negative Syndrome Scale. Inpatients and outpatients were compared with regard to the use of antipsychotics and benzodiazepines. To compare different drugs, chlorpromazine and diazepam equivalents were calculated. Results: Lack of efficacy and side effects were the main reasons for initiating new antipsychotic medication. Combined evaluation of all antipsychotic compounds by meta-analysis resulted in a significant effect of the treatment setting, with inpatients receiving higher doses than outpatients. In addition, inpatients were prescribed benzodiazepines more often and in higher doses than outpatients. Conclusions: Both antipsychotics and benzodiazepines were prescribed at higher doses in an inpatient setting. Moreover, benzodiazepines were prescribed more frequently to inpatients. Accordingly, the treatment setting needs to be taken into consideration in treatment recommendations for schizophrenia spectrum disorders.